Obstacle's effects and their location inside the square cavity on the thermal performance of Cu–Al2O3/H2O hybrid nanofluid - Hachichi, Farid; Belghar, Nourredine; Kamel, Chadi; Saleh, Momen S. M.; Kadja, Mahfoud; Lachi, Mohammed; Chamkha, Ali J. (Heat Transfer, 2023)
The current study focuses on the effect of obstacles and their positioning within the square cavity (L = H) on heat exchange. This work considers heating the cavity's bottom wall to a steady, high temperature. The top wall of the cavity is adiabatic, while the two vertical side walls are cooled. Four cases are explored under these conditions: the first case is a square-shaped cavity holding a square-shaped obstacle h = l = 0,15 L, while the other three cases, respectively, each include two, three, and four square obstacles. The cavity was filled with Cu–Al2O3/H2O hybrid nanofluid with a volume fraction φ = 0.03. Numerical results for laminar and stationary flow regimes with Rayleigh numbers 104 ≤ Ra ≤ 106. The finite volume approach solves the governing equations numerically. The findings show that the number of square obstacles within the square-shaped cavity significantly impacts heat exchange and hybrid nanofluid flow. The second example, with two square obstacles, improves heat exchange more than other cases with one to four barriers. In the second example, the obstacle location at the plane Y = 0.25H is suitable and helps boost heat transmission of the hybrid nanofluid. The ideal obstacle position in the fourth scenario, which has four square barriers, is at the plane Y = 0.75H.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/htj.22834
Keywords: Rayleigh number; hybrid nanofluid; obstacle; square cavity; thermal performance